PENGARUH KEPEMIMPINAN BERBASIS NILAI DAN BUDAYA KERJA TERHADAP KEPUASAN KERJA GURU DI SMP NEGERI DI KECAMATAN SALO KABUPATEN KAMPAR - AZMI AZMI; RR. SRI KARTIKOWATI; SUDIRMAN AS SUDIRMAN AS (Universitas Riau, 2017)
This study aims to analyze (1) Value-based leadership directly affect positivelyand significantly to the work culture (2) Value-based leadership directly affect positively andsignificantly to job satisfaction of teachers (3) Working culture directly affect positively andsignificantly to job satisfaction of teachers (4) value-based leadership and work culture positiveand significant direct effect on job satisfaction of teachers in junior high school sub-district SaloKampar regency. The population of as many as 95 teachers. With cluster random sampling,sample obtained 77 respondents. Data analysis using path analysis (path analysis). The finalconclusion (1) The values-based leadership has positive influence on the work culture at 96.3%,meaning that the higher the value of value-based leadership can create a better working culture(2) a value-based leadership positive effect on job satisfaction of teachers 96.5 %, meaningthat the higher the value of value-based leadership the higher the job satisfaction of teachers tothe school (3) working culture positive effect on job satisfaction of teachers by 95%, that is, thebetter the work culture that exist in school, the higher the job satisfaction of teachers in theseschools (4) the values-based leadership and work culture positive effect on job satisfaction ofteachers by 96.8%, meaning that the higher the value of value-based leadership and workculture that is created in school, the higher the job satisfaction of teachers in junior secondaryschool in the District Salo, Kampar